Conversational Agent: Technological Means to Innovate the Educational Environment? - Salas-Rueda, Ricardo-Adán; Luna-García , Ismael; Santiago-de-la-Torre, Julieta; Cervantes-de-la-Cruz , Karina-Elizabeth (Revista Ecos de la Academia, 2025)
The general aim of this mixed study was to analyze the use of the Conversational Agent on Financial Mathematics (ACMF) in the Bachelor of Earth Sciences considering data science. This research proposes the use of this conversational agent to innovate the teaching-learning process through the interaction with the user in the form of voice and text. ACMF uses a function obtained from the Deep learning algorithm to adapt the content. The results of this study indicate that ACMF favors the aspects of the personalized learning, motivation and active role. The Random forest algorithm built two predictive models on the use of this conversational agent where the sex and age influence the forecast of the motivation and active role. The benefits of ACMF are the understanding of mathematical formulas, review of the school topics, creation of an innovative and pleasant environment, flexibility of time and personalized learning. In conclusion, tools related to artificial intelligence are revolutionizing the organization of the educational practices in the 21st century. In particular, ACMF offers the communication with the student in the form of voice and text to learn the topics of mathematics.